Mirror Self-Recognition in Pigeons: Beyond the Pass-or-Fail Criterion - Wittek, Neslihan; Matsui, Hiroshi; Kessel, Nicole; Oeksuez, Fatma; Güntürkün, Onur; Anselme, Patrick (Frontiers in Psychology, 2021)
Spontaneous mirror self-recognition is achieved by only a limited number of species, suggesting a sharp “cognitive Rubicon” that only few can pass. But is the demarcation line that sharp? In studies on monkeys, who do not recognize themselves in a mirror, animals can make a difference between their mirror image and an unknown conspecific. This evidence speaks for a gradualist view of mirror self-recognition. We hypothesize that such a gradual process possibly consists of at least two independent aptitudes, the ability to detect synchronicity between self- and foreign movement and the cognitive understanding that the mirror reflection is oneself. Pigeons are known to achieve the first but fail at the second aptitude. We therefore expected them to treat their mirror image differently from an unknown pigeon, without being able to understand that the mirror reflects their own image. We tested pigeons in a task where they either approached a mirror or a Plexiglas barrier to feed. Behind the Plexiglas an unknown pigeon walked at the same time towards the food bowl. Thus, we pitched a condition with a mirror-self and a foreign bird against each other, with both of them walking close towards the food bowl. By a detailed analysis of a whole suit of behavioral details, our results make it likely that the foreign pigeon was treated as a competitor while the mirror image caused hesitation as if being an uncanny conspecific. Our results are akin to those with monkeys and show that pigeons do not equal their mirror reflection with a conspecific, although being unable to recognize themselves in the mirror.